Physical Characteristics of Activated Carbon Derived from Durian Shell - THAM, Y.J.; ABDUL LATIF*, PUZIAH; ABDULLAH, A.M.; TAUFIQ-YAP†, Y.H. (Asian Journal of Chemistry, 2024)
Durian shells are easily available agricultural by-products and itslarge quantities of generation make it a potential source for productionof low cost activated carbon. This study was performed to determinethe characteristics of activated carbon prepared from durian shell. Ultimateand proximate analysis for raw material was determined. The durianshell activated carbon was prepared from impregnating the sample in 5,10, 20 and 30 % (v/v) concentration of phosphoric acid for 24 h, followedby carbonization at different temperatures in nitrogen atmosphere. Theresults showed that various treatment conditions affect the percentageof yield, surface area and pore structure. The highest BET surface area1404 m2/g was obtained at 30 % of acid concentration, 500 °C and 20 minof heating.